Zoonotic diseases: New directions in human–animal pathology. (8th March 2021) - Bendrey, Robin; Martin, Debra
Abstract: Zoonotic diseases—human diseases of animal origin—represent one of the world's greatest health challenges, both today and in the past. Since the Neolithic, zoonotic diseases have been one of the major factors shaping and influencing human adaptation. Archaeology is ideally situated to provide the long view on human–animal–pathogen relationships through combining cultural, environmental and biological datasets, yet long‐term studies of linked human and animal records have often been overlooked and undertheorized. The seven papers in this special issue "Zoonotic diseases: New directions in human–animal pathology" cover a range of diseases caused by bacterial, viral, and parasitic pathogens, from case studies drawn from across Europe, Asia, Africa and the Americas. They speak to the diversity of human–animal–environment interactions that shaped disease emergence and transmission. They also review methodological advancements relating to disease identification and interpretation and discuss interdisciplinary approaches to effectively investigate these complex processes in the past. This introduction highlights their key themes and outcomes and identifies research priorities moving forward.